2020
DOI: 10.3390/molecules25061288
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous Hinge-Bending Motions of Angiotensin I Converting Enzyme: Role in Activation and Inhibition

Abstract: The inhibition of human angiotensin I converting enzyme (ACE) has been regarded as a promising approach for the treatment of hypertension. Despite research attempts over many years, our understanding the mechanisms of activation and inhibition of ACE is still far from complete. Here, we present results of all atom molecular dynamics simulations of ACE with and without ligands. Two types of inhibitors, competitive and mixed non-competitive, were used to model the ligand bound forms. In the absence of a ligand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In contrast, with the N- and C-domains of ACE only crystallising in the closed conformation until recently, the opening of ACE could only be predicted using molecular modelling and comparisons with ACE2. There have been several of these molecular modelling studies using normal mode analysis and molecular dynamics examining not only the domain opening directly, but also the effect of site-directed mutations on this movement [ 92 , 101 , 103 ]. With the recent crystal structure of ACE N-domain in the open conformation [ 91 ], and re-examination of the earlier C-domain structure in complex with BPPb that was shown to have opened slightly [ 69 ], it can be confirmed that all these domains open with the same mechanism.…”
Section: Hinge Mechanism Of Ace2 and Acementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, with the N- and C-domains of ACE only crystallising in the closed conformation until recently, the opening of ACE could only be predicted using molecular modelling and comparisons with ACE2. There have been several of these molecular modelling studies using normal mode analysis and molecular dynamics examining not only the domain opening directly, but also the effect of site-directed mutations on this movement [ 92 , 101 , 103 ]. With the recent crystal structure of ACE N-domain in the open conformation [ 91 ], and re-examination of the earlier C-domain structure in complex with BPPb that was shown to have opened slightly [ 69 ], it can be confirmed that all these domains open with the same mechanism.…”
Section: Hinge Mechanism Of Ace2 and Acementioning
confidence: 99%
“…The ACE N-domain structure did not show as large a degree of opening as ACE2, and it was concluded that the N-domain had crystallised in a partially open conformation, possibly stabilised by residues at the subdomain interface coordinating magnesium ions from the crystallisation conditions. One of the molecular dynamics studies using an ACE C-domain structure with the co-crystallised Ang II ligand removed, showed that during a long 400 ns simulation the C-domain went through various states of closed, partially open, and fully open conformations that were similar to those of the ACE2 structures [ 103 ].…”
Section: Hinge Mechanism Of Ace2 and Acementioning
confidence: 99%
“…A recent molecular dynamics study [28] using the Ang II-cACE complex closed structure [34] showed that when the Ang II peptide was removed prior to a long 400-ns simulation, the cACE structure went A previously reported BPPb-cACE (bradykininpotentiating peptide b) complex structure showed that the zinc-binding residues (His-383, His-387 and Glu-411) underwent a conformational change and moved away from the usual ligand binding site, and it was concluded this may have been due to not having an active-site zinc ion bound [34]. These residues are all located within subdomain 1 and can link the two subdomains when they bind a zinc ion through the bound ligand.…”
Section: Comparison Of Nace Cace and Ace2 Subdomain Dynamicsmentioning
confidence: 99%
“…The two subdomains of ACE2 open in a 'clam shell'-like manner, resulting in a deep groove leading to the binding site. There have been several molecular dynamics studies that have indicated that ACE is able to open in a similar way [27][28][29]. In particular, the lid was identified as one of the six hinge regions within each domain using normal mode analysis [29].…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make the following corrections to the paper [ 1 ]: During the final preparation of the manuscript, the family name of the first author was omitted; also, the affiliation and the e-mail of the first author were not correctly input. We would thus like to make following changes to the paper [ 1 ], as follows:…”
mentioning
confidence: 99%